Dimensional accuracy of micro-electro discharge milling - Ali, Mohammad Yeakub; Abd. Rahman, Mohamed; Zunairi, Siti Nur Zuhaida; Banu, Asfana (IOP Publishing, 2017)
This paper investigates the dimensional accuracy and tool wear rate (TWR) in micro electro discharge (micro-ED) milling of stainless steel (S304) workpiece and tungsten as the tool electrode with control parameter; voltage and feed rate. Dimensional accuracy is represented by the difference of micro-channel width between the two ends of the channel. The TWR and the micro-channel width data are analyzed and empirical model are developed. The optimum values for minimum TWR and minimum micro-channel width are found to be 91 V voltage and 10 μm/s feed rate.